Accuracy of single-photon emission computed tomography in differentiating frontotemporal dementia from Alzheimer's disease. Issue 4 (8th December 2006) - McNeill, R; Sare, G M; Manoharan, M; Testa, H J; Mann, D M A; Neary, D; Snowden, J S; Varma, A R
Abstract : Background: Alzheimer's disease (AD) and frontotemporal dementia (FTD) are the commonest causes of presenile dementia. In the absence of a biological marker, diagnosis is reliant on clinical evaluation. Confirmation is often sought from neuroimaging, including single-photon emission computed tomography (SPECT). Most previous SPECT studies lack pathological validation. Aim: To examine the accuracy of SPECT in differentiating FTD from AD in patients with subsequent pathological confirmation. Methods: Technetium-99-labelled hexamethyl propylene amine oxime SPECT images obtained at initial evaluation in 25 pathologically confirmed cases of FTD were examined. These images were visually rated by an experienced blinded nuclear medicine consultant and compared with those of 31 patients with AD, also with pathological validation. Results: A reduction in frontal cerebral blood flow (CBF) was more common in FTD and was of diagnostic value (sensitivity 0.8, specificity 0.65 and likelihood ratio (LR) 2.25; 95% CI 1.35 to 3.77). A pattern of bilateral frontal CBF reduction without the presence of associated bilateral parietal CBF change is diagnostically more accurate (sensitivity 0.80, specificity 0.81 and +LR 4.13, 95% CI 1.96 to 8.71). Diagnostic categorisation (FTD or AD) on the basis of SPECT alone was less accurate than clinical diagnosis (based on neurology and detailed neuropsychological evaluation). One patient with FTD was initially clinically misdiagnosed as AD, owing to the lack of availability of full neuropsychological assessment. However, SPECT correctly diagnosed this patient, providing a diagnostic gain of 4%. Conclusion: Technetium-99-labelled hexamethyl propylene amine oxime SPECT CBF patterns provide valuable information in the diagnosis of FTD and AD. These data can be better used as an adjunct to clinical diagnosis if pathology is to be correctly predicted in life.